Motivation to Change in the Course of a Pilot Study of a Step-Down Treatment Approach of Inpatient and Anorexia Nervosa-Specific Home Treatment and Its Effects on Treatment Outcome - Heider, Kathrin Sophie; Dempfle, Astrid; Altdorf, Sophie; Herpertz-Dahlmann, Beate; Dahmen, Brigitte (Frontiers in Psychiatry, 2021)
Introduction: Anorexia nervosa (AN) is a serious mental disorder that typically manifests in adolescence. Motivation to change is an important predictor for treatment outcome in adolescent AN, even though its development over the often long therapeutic process, with transitions between treatment settings, has not yet been studied. In this pilot study, the course of motivation to change and its effect on treatment outcome were investigated over the course of a step-down treatment approach during a 12-month observation period. Methods: Twenty-one adolescents admitted to inpatient treatment because of AN received multidisciplinary home treatment (HoT) with several weekly visits after short inpatient stabilization. Eating disorder (ED-)specific cognitive [Eating Disorder Inventory 2 (EDI-2) subscales] and physical [% expected body weight (%EBW)] illness severity and motivation to change [Anorexia Nervosa Stages of Change Questionnaire (ANSOCQ)] were assessed at the time of admission, discharge from hospital, at the end of HoT, and at a 12-month follow-up. Changes in motivation over time and its relationship with treatment outcome were investigated. Results: Mean motivation to change improved significantly over the course of treatment from the contemplation stage [2nd stage, mean ANSOCQ sum score 47.26 (SD 17.60)] at admission to the action stage [4th stage, mean ANSOCQ sum score 77.64 (SD 18.97)] at the end of HoT (p < 0.001) and remained stable during the follow-up period. At each assessment, higher motivation to change was significantly correlated with lower ED-specific cognitive illness severity (Spearman ρs: −0.53 to −0.77, all p < 0.05). Only pretreatment motivation to change significantly predicted ED-specific cognitive illness severity after the first inpatient treatment phase when taking prior illness severity into account. Conclusions: Motivation to change is an important aspect of treatment success in adolescent AN, especially in the early phase of treatment. In addition, home treatment contributed significantly to a higher motivation. Further longitudinal research into how motivation to change in adolescent patients with AN is related to outcome in this often severe and enduring disease and into targeted therapeutic strategies and interventions that reliably enhance the motivation to change in adolescent patients with AN seems promising.